Indicadores de desempenho físico e tático-técnico de atletas do voleibol de praia em diferentes categorias - Pontes, Nayara Elis Cabral (2019)
The present investigation analyzed indicators of physical and tactical-technical performance in beach volleyball athletes in different categories: Under-15 (11 to 14 years old, n = 21), Under-18 (15 to 17 years old, n = 24) and Senior (≥ 18 years old, n = 22) of both sexes. This non-experimental, cross-sectional and correlational-causal research aimed to describe relationships between different physical and tacticaltechnical variables of beach volleyball athletes. Initially, the morphological (anthropometry and body composition) and neuromuscular dimensions (lower limb power, upper limb strength, agility and velocity) were collected; Then, the metabolic dimension (aerobic capacity) was collected through VO2 and, finally, a sporting event of a friendly level was elaborated among the athletes selected by categories to perform the observational analysis of the tactical performance. technician. In the statistical analysis, comparison between categories was performed using one-way ANOVA, correlations by Pearson's test (for normal distribution), or Spearman's test (for nonnormal distribution) and the explanation of a model for each category was verified by regression. multiple, the significance adopted was P≤0.05. The results of this study revealed that morphological and physical performance characteristics of beach volleyball athletes are different between categories and these characteristics presented important relationships with physical performance in all categories. It was also found that there is a homogeneity in tactical-technical performance, especially between the Under-15 and senior categories, female; whereas the tactical-technical performance for raising and attacking was superior for the senior male category compared to the other categories; and that the athlete's experience in beach volleyball seems to influence the tactical-technical performance predominantly in the serve for the senior male and Under-18 female groups and the survey for the Under-15 group. In addition, explanatory models of performance coefficients from performance variables found associations in females for the serve and withdrawal fundamentals, in the under-15 and senior category and for the attack basis in the senior category, and in the male gender. There were associations in the three categories for the reception plea, for the Under-15 and Senior plea, and finally for the attack plea in the Senior category. In conclusion, these findings may be useful for the training process of athletes in this sport, revealing specificities of physical and tactical-technical behavior. Thus, this research will assist beach volleyball professionals and athletes in the elaboration and monitoring of training programs, besides collaborating with the scientific production inherent to the area